The Transformation of the Independent Curriculum: An Analysis of Learning Crisis Recovery and Its Relevance in 21st Century Learning in the Society 5.0 Era - Matnur Ritonga; Eman Ahmed; Mohammad Shahril (Universitas Darunnajah Jakarta, Indonesia, 2025)
This study aims to analyze the transformation of the Merdeka Curriculum as a solution to address the learning crisis caused by the COVID-19 pandemic and its relevance within the context of 21st-century learning in the era of Society 5.0. The method used is a literature study with a qualitative analysis of recent academic sources. The findings indicate that the Merdeka Curriculum provides flexible learning, emphasizes the development of 21st-century skills, and incorporates digital technology, although there are challenges related to infrastructure and human resource readiness. This curriculum application focuses on project-based and character education, aligning well with the current digital era's needs and helping prepare students to become adaptive and innovative learners.